Electroacupuncture at “Zusanli(ST36)” alleviates 5-fluorouracil-induced renal injury in colorectal cancer-bearing mice by exerting effects on oxidative stress, inflammatory responses, and cell apoptosis - ZHANG, Xue-jun; LIN, Jiu-mao; CHEN, Shi-lan; LIN, Chen-jie; PENG, Jiao; YANG, Xiao-dan; ZHAO, Jin-yan (World journal of acupuncture-moxibustion, 2023)
To observe the effect of electroacupuncture at “Zusanli (ST36)” on 5-fluorouracil (5-FU)-induced renal injury in colorectal cancer-bearing mice, and to further investigate its effects on oxidative stress, inflammatory responses, and cell apoptosis in mouse renal tissue. Thirty-five male BALB/c mice were randomly divided into five groups of seven mice each, namely the control, CT26, 5-FU, sham point (SP), and ST36 (which received EA at the “ST36”) groups. With the exception of the control group, each group was subjected to establishment of a subcutaneous implantation tumor model using the murine CT26 colorectal cancer cell line. Once the models were successfully established, the 5-FU, SP, and ST36 groups received 5-FU injection solution intraperitoneally at a dose of 5 mg/mL once every three days over a 21-day period. Mice in the SP and ST36 groups additionally received an EA intervention after each intraperitoneal 5-FU injection. EA were performed on mice of the SP group at bilateral sham acupoints and on mice of the ST36 group at the bilateral “ST36” using the continuous wave mode at a frequency of 2 Hz for a duration of 5 min, intervention was administered once every two days for a duration of 21 days. Samples were collected from the mice at the end of the experiment. The pathological morphology of the renal tissue was observed using hematoxylin and eosin (HE) staining; the contents of creatine (Cre), blood urea nitrogen (BUN) and malondialdehyde (MDA), and superoxide dismutase (SOD) activity were measured using biochemical assays; the expression and nuclear translocation of nuclear factor kappa B p65 subunit (NF-κB p65) were measured by immunofluorescence; the expression levels of tumor necrosis factor alpha (TNF-α), interleukin-6 (IL-6), and interleukin-1β (IL-1β) in serum were measured by ELISA; cell apoptosis in renal tissue was detected using the TUNEL assay; and the expression levels of the anti-B-cell lymphoma/leukemia 2 (Bcl-2), Bcl-2-associated X protein (Bax), cleaved caspase-3, cleaved caspase-9, and cytochrome C (cyt c) in renal tissue were measured by Western blotting. Compared with the control group, mice of the CT26 group showed a significant increase in serum Cre content (P<0.01), but the difference in BUN content was not statistically significant (P>0.05). HE staining of renal tissue revealed clear structures with normal glomerular and renal tubular morphology. SOD activity was decreased (P<0.01); MDA content was increased, but the increase was not statistically significant (P>0.05). Differences in NF-κB p65 protein expression in the cytoplasm of renal tissue and serum levels of TNF-α, IL-6, and IL-1β were not statistically significant (all P>0.05). Results of immunofluorescent TUNEL staining indicated an absence of significant cell apoptosis. In the renal tissue, Bcl-2 protein expression was slightly increased (P<0.05), and the expression levels of Bax (P<0.01), cleaved caspase-3 (P>0.05), cleaved caspase-9 (P<0.01), and cyt c (P>0.05) were increased. Compared with the CT26 group, mice of the 5-FU group exhibited an increase in Cre (P<0.01) and BUN (P<0.05) content. HE staining of renal tissue revealed the presence of glomerular atrophy and dilated Bowman's capsular spaces. SOD activity was significantly decreased (P<0.01), while the increase of MDA content was not significant (P>0.05). The expression of NF-κB p65 in the nucleus and serum TNF-α, IL-6, and IL-1β levels showed significant increases (P<0.05). The cell apoptosis level was significantly increased. The protein expression of Bcl-2 (P<0.05), Bax (P<0.01), cleaved caspase-9 (P<0.01), and cyt c (P<0.05) was significantly increased. Compared with the 5-FU group, the ST36 group showed decreased serum Cre and BUN levels (both P<0.01). HE staining of renal tissue showed less renal tissue injury and less dilation of renal capsular cavities. SOD activity was significantly higher (P<0.01), while MDA content was lower (P<0.05). Nuclear expression of NF-κB p65 and serum TNF-α (P<0.05), IL-6 (P<0.05), and IL-1β (P<0.01) levels were lower. The cell apoptosis level was decreased relative to the 5-FU group. Bcl-2 protein expression was significantly increased (P<0.01), while the protein expression levels of Bax (P<0.01), cleaved caspase-3 (P<0.01), cleaved caspase-9 (P<0.01), and cyt c (P<0.05) also were reduced. EA at “ST36” attenuated 5-FU-induced renal injury in colorectal cancer-bearing mice. The mechanism may be related to the regulation of renal oxidative stress, alleviation of inflammatory responses, and inhibition of cell apoptosis.